Genome analysis of a plasmid-bearing myxobacterim Myxococcus sp. strain MxC21 with salt-tolerant property - Liu, Lin; Xu, Fengjuan; Lei, Jinhui; Wang, Peiwen; Zhang, Lei; Wang, Jihong; Zhao, Jingya; Mao, Dongmei; Ye, Xianfeng; Huang, Yan; Hu, Gang; Cui, Zhongli; et al. (Frontiers in Microbiology, 2023)
Myxobacteria are widely distributed in various habitats of soil and oceanic sediment. However, it is unclear whether soil-dwelling myxobacteria tolerate a saline environment. In this study, a salt-tolerant myxobacterium Myxococcus sp. strain MxC21 was isolated from forest soil with NaCl tolerance greater than 2% concentration.Under 1% salt-contained condition, strain MxC21 could kill and consume bacteria prey, and exhibited complex social behaviors like S-motility, biofilm and fruiting body formations, but adopted an asocial living pattern with the presence of 1.5% NaCl. To investigate the genomic basis of stress tolerance, the complete genome of MxC21 was sequenced and analyzed. Strain MxC21 consists of a circular chromosome with a total length of 9.13 Mbp and a circular plasmid of 64.3 kb. Comparative genomic analysis revealed that the genomes of strain MxC21 and M. xanthus DK1622 shares high genome synteny, while no endogenous plasmid was found in DK1622. Further analysis showed that about 21% of its coding genes from the genome of strain MxC21 predominantly are associated with signal transduction, transcriptional regulation and protein folding that involving in diverse niche adaptation like salt tolerance, which enable social behavior like gliding motility, sporulation, and predation. Meantime, high number of genes are also found to be involved in defense against oxidative stress and production of antimicrobial compounds. All these functional genes may responsible for the potential salt-toleration. Otherwise, strain MxC21 is the second reported myxobacteria containing indigenous plasmid, while only a small proportion of genes were specific to the circular plasmid of strain MxC21, and most of them were annotated as hypothetical proteins, which may have direct relationship with the habitat adaptation of strain MxC21 under saline environment. This study provides an inspiration of the adaptive evolution of salt-tolerant myxobacterium, and facilitates a potential application in the improvement of saline soil in the future.